2010
DOI: 10.1097/ta.0b013e3181e291e9
|View full text |Cite
|
Sign up to set email alerts
|

Should Age Be a Factor to Change From a Level II to a Level I Trauma Activation?

Abstract: Patients with an ISS between 0 and 15 are often triaged to Level II activation. Our data would suggest that patients older than 60 years should be a criterion for the highest level of trauma activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 20 publications
2
27
0
1
Order By: Relevance
“…4 Data from the National Trauma Databank have shown that elderly trauma patients have a threefold increase in morbidity and a fivefold increase in mortality with minor ISS, whereas they have a twofold increase in morbidity and a fourfold increase in mortality with major ISS. 5 Another study showed an 11.4% mortality rate in trauma patients age older than 65 years compared with patients aged 18 to 35 years who only had a mortality rate of 2.4%. 4 The trauma death rate per 100,000 people per year is 56.0 for all age groups combined.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…4 Data from the National Trauma Databank have shown that elderly trauma patients have a threefold increase in morbidity and a fivefold increase in mortality with minor ISS, whereas they have a twofold increase in morbidity and a fourfold increase in mortality with major ISS. 5 Another study showed an 11.4% mortality rate in trauma patients age older than 65 years compared with patients aged 18 to 35 years who only had a mortality rate of 2.4%. 4 The trauma death rate per 100,000 people per year is 56.0 for all age groups combined.…”
Section: Discussionmentioning
confidence: 97%
“…2,4 Geriatric trauma patients have significantly worse outcomes compared with younger patients. 5 Therefore, trauma care given to these patients should be distinctively different from care given to their younger cohorts. Thus, the purpose of this study was to evaluate the effectiveness of a multidisciplinary trauma service model (G-60) aimed at improving elderly trauma patient outcomes.…”
mentioning
confidence: 99%
“…Ideally, patients with major trauma are triaged to the highest level of trauma care, that is, a level I trauma team activation (TTA), based on triage guidelines. However, some patients who present with certain risk factors are not assigned a level I TTA despite the severity of injuries 8. The group of patients with an ISS >15 who do not receive level I TTA are termed “undertriaged”.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we found that older age was associated with the nonuse of the call center and delay in time to definitive care. Shifflette et al 9 found that geriatric patients have worse outcomes, even with minimal injury (ISS G 15) and suggest that patients older than 60 years be activated at the highest level. The lack of call center use and outcomes in this patient population need further exploration.…”
Section: Discussionmentioning
confidence: 98%